Botanic component in training bachelors of ecology at the Siberian State University of Geosystems and Technologies (SSUGIT) - Fershalova Tatyana (EDP Sciences, 2021)
Ecologist is among the specialties in high demand, especially under the conditions of urban environment. Plant knowledge is an essential component in preparing ecology students to academic, research and development activities. Plants knowledge gained through education is an important element for diagnostics and improvement of the ecological environment affected by various anthropogenic and natural factors. Education involves practical courses aimed at consolidation of the skills for plant identification, phyto indexing and formulation of recommendations on environmental optimization. It is shown that the application of interdisciplinary approach to the formation of universal competence through learning botany is relevant.